If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -20x + 2 = 3x Reorder the terms: 2 + -20x = 3x Solving 2 + -20x = 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 2 + -20x + -3x = 3x + -3x Combine like terms: -20x + -3x = -23x 2 + -23x = 3x + -3x Combine like terms: 3x + -3x = 0 2 + -23x = 0 Add '-2' to each side of the equation. 2 + -2 + -23x = 0 + -2 Combine like terms: 2 + -2 = 0 0 + -23x = 0 + -2 -23x = 0 + -2 Combine like terms: 0 + -2 = -2 -23x = -2 Divide each side by '-23'. x = 0.08695652174 Simplifying x = 0.08695652174
| 22x=150 | | 12y=11(y+3) | | X/31=4+19 | | 4x+2-3=11 | | 6-6x-3=-17+4x-10 | | 7x+12=-5x-8 | | -2x-14=3x+11 | | 7x+12=-5-8 | | x^2-16+48=0 | | 1/5x+2=13 | | 3x+2.5=7 | | 2(x+4)=3(x+5) | | 2*4-2y=-4 | | 8x-3y+21=0 | | 15y=14(y+12) | | X/23=-39+3 | | 10x+3-9x=10 | | 2(6+a)= | | -5-7=-4+x | | x+3x=1200 | | 6(z-2)+5z-4= | | 5(q+7)= | | X-6x+8x-9x= | | 6q+2q= | | -(8y+2)-(-7y-6)=1 | | -(8y+2)-(-7-6)=1 | | 9y=8(y+1) | | 2[3-2(4-5)]= | | 396=3000(0.044)x | | 5/x+3/4=11/8 | | 9y-6=-3 | | (128x^13w^20)^1/5 |